2019
DOI: 10.1073/pnas.1914426116
|View full text |Cite
|
Sign up to set email alerts
|

Oral ionic liquid for the treatment of diet-induced obesity

Abstract: More than 70% of American adults are overweight or obese, a precondition leading to chronic diseases, including diabetes and hypertension. Among other factors, diets with high fat and carbohydrate content have been implicated in obesity. In this study, we hypothesize that the choline and geranate (CAGE) ionic liquid can reduce body weight by decreasing fat absorption through the intestine. In vitro studies performed using docosahexaenoic acid (DHA), a model fat molecule, show that CAGE forms particles 2 to 4 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“… Marked changes in the gut microbiome have been observed in mice exposed to imidazolium-based ILs via drinking water; however, only mild hepatic and renal effects were observed (Young et al 2020 ). As a system biology potential application of ILs, it has been shown that in rats, oral delivery of a choline-based IL prevent the absorption of fat molecules through intestinal tissue, potentially providing a feeling of satiety (Nurunnabi et al 2019 ). Biochemistry and histology results indicated that the choline-based IL used in the study was tolerated by the rats.…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
See 2 more Smart Citations
“… Marked changes in the gut microbiome have been observed in mice exposed to imidazolium-based ILs via drinking water; however, only mild hepatic and renal effects were observed (Young et al 2020 ). As a system biology potential application of ILs, it has been shown that in rats, oral delivery of a choline-based IL prevent the absorption of fat molecules through intestinal tissue, potentially providing a feeling of satiety (Nurunnabi et al 2019 ). Biochemistry and histology results indicated that the choline-based IL used in the study was tolerated by the rats.…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
“…As a system biology potential application of ILs, it has been shown that in rats, oral delivery of a choline-based IL prevent the absorption of fat molecules through intestinal tissue, potentially providing a feeling of satiety (Nurunnabi et al 2019 ). Biochemistry and histology results indicated that the choline-based IL used in the study was tolerated by the rats.…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…ILs can extract specific active compounds from plants for pharmaceutical, nutritional, and cosmetic applications, such as the antimalarial drug artemisinin from the plant Artemisia annua [6]. Improvement of the gastrointestinal absorption of drugs by IL conversion [7][8][9] and improvement of the solubility of poorly soluble drugs using ILs [10,11] have been actively studied. Regarding enhancement of the percutaneous absorption of drugs examined in Pharmaceutics 2020, 12, 427 2 of 10 his study, it has been reported that skin permeation of drugs was enhanced by IL formation [12][13][14][15][16][17] and IL micelle formation as well [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…We thank Peiretti et al (1) for their interest in our work (2) and for the suggestions for follow-up research. Peiretti et al (1) ask about the role of reduced food consumption in the observed effect on reduced weight gain.…”
mentioning
confidence: 98%